2021
DOI: 10.1016/j.dhjo.2021.101110
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of poor mental health and stressors during the COVID-19 pandemic, by disability status: A cross-sectional analysis

Abstract: Background Evidence from previous public health emergencies indicates that adults with disabilities have higher risk for morbidity (physical and mental) and mortality than adults without disabilities. Objective To provide estimates of mental health indicators and stressors for US adults by disability status during April and May 2020, shortly following the emergence of the COVID-19 pandemic. Methods We analyzed data from Porter Novelli View 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 42 publications
6
69
2
2
Order By: Relevance
“…Additionally, Zhang et al found personal financial loss to be significantly higher among students with disabilities (40). Interestingly, among the general population of adults, Okoro et al found non-disabled persons were significantly more likely to report experiencing job or income loss compared to adults with disabilities (55). These findings may contrast with our study due to the differences in how these data were collected and reported.…”
Section: Psychosocial Stressorscontrasting
confidence: 99%
See 1 more Smart Citation
“…Additionally, Zhang et al found personal financial loss to be significantly higher among students with disabilities (40). Interestingly, among the general population of adults, Okoro et al found non-disabled persons were significantly more likely to report experiencing job or income loss compared to adults with disabilities (55). These findings may contrast with our study due to the differences in how these data were collected and reported.…”
Section: Psychosocial Stressorscontrasting
confidence: 99%
“…This aligns with reports of mental distress among disabled adults outside of the academic setting. In April and May 2020, Okoro et al found that adults with any disability type were three times more likely to report depressive symptoms compared to non-disabled participants (55).…”
Section: Psychosocial Stressorsmentioning
confidence: 99%
“…In opposite, in the general population the ones with risk factors or/and disabilities actually improved their psychological health most over the course of the pandemic. This may also relate to the fact that patients with maximized challenges may experience more negative health developments while individuals with disabilities or risk factors from the general population may rather perceive all the hygiene measures as protective and pleasing their needs [49].…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 , 36 Although previous studies have examined whether people with disabilities perceive that the COVID-19 pandemic decreased their psychosocial well-being, 13 , 14 , 15 , 16 , 37 only a few have focused on various types of disabilities. 38 As a response to this lack of information, the present study investigated whether people with various disabilities (mobility, vision, hearing, and cognitive) and with any disabilities reported COVID-19-related negative effects on their psychosocial well-being—loneliness, decreased social contact, decreased hope for the future, and concern about being infected with the virus—more often than those without disabilities. We also investigated whether effects of disabilities on concerns about infection varied across different ages— that is, the interaction effect of age and disabilities on concern about infection.…”
Section: Introductionmentioning
confidence: 99%